Multiscale testing-analysis of asphaltic materials considering viscoelastic and viscoplastic deformation. Issue Volume 18:Issued 9(2017) (2nd September 2017) - Im, Soohyok; You, Taesun; Ban, Hoki; Kim, Yong-Rak
Abstract: Fine aggregate matrix (FAM) is a phase consisting of asphalt binder, air voids, fine aggregates and fillers. It acts as a primary phase in evaluating the damage and deformation of entire asphalt concrete mixtures. The simplicity, repeatability and efficiency of the FAM testing make it a very attractive specification-type approach for evaluating the performance characteristics of the entire asphalt concrete mixtures. This study explores a linkage in the deformation characteristics between the two length scales: asphalt concrete mixture scale and its corresponding FAM scale. To that end, a simple creep-recovery test was conducted for both mixtures (i.e. asphalt concrete mixture and its corresponding FAM phase) at various stress levels. Test results were compared and analysed using Schapery's single-integral viscoelastic theory and Perzyna-type viscoplasticity with a generalised Drucker–Prager yield surface. In particular, stress-dependent nonlinear viscoelastic and viscoplastic behaviours were characterised in addition to linear viscoelastic deformation characteristics, because the nonlinear viscoelastic and viscoplastic behaviours are considered significant in asphalt pavements that are subjected to heavy vehicle loads and elevated service temperatures. With a limited scope and test-analysis results at this stage, it was found that there is a strong link between the FAM and asphalt concrete in (linear and nonlinear) viscoelastic and viscoplastic deformation characteristics. This implies that the viscoelastic stiffness characteristics and viscoplastic hardening of typical asphalt concrete mixtures could be estimated or predicted from the simple FAM-based testing-analysis method, which can significantly reduce the experimental–analytical efforts required for asphalt concrete mixtures.